Pengaruh Motivasi, Kepuasan Kerja dan Komunikasi Interpersonal Terhadap Keterlibatan Pegawai Bapenda Kota Semarang - Wulandari, Wulandari; Fauzan, Mohammad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze and explain (1) the influence of work motivation on employee engagement, (2) how the effect of job satisfaction on employee engagement and (3) the influence of interpersonal communication on employee engagement in the Semarang City Bapenda.  This research is a type of explanatory research. The research sample was 100 people.  The data collection technique uses a questionnaire distributed through google forms. Data analysis uses multiple linear regression with the help of SPSS software. The results of the research findings show that (1) work motivation has a positive effect on employee  engagement, (2) job satisfaction has a positive effect on employee  engagement, (3) Interpersonal communication has a positive effect on employee engagement of the Semarang City Bapenda.